2002
DOI: 10.1016/s1062-1458(02)00946-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clinical syndrome acuity on the differential response to 2 glycoprotein IIb/IIIa inhibitors in patients undergoing coronary stenting. The TARGET trial

Abstract: Background-Although glycoprotein IIb/IIIa inhibitors have been shown to reduce periprocedural and late ischemic events in patients undergoing stent implantation, the relative safety and efficacy of different agents in this class is less established. Also unknown is whether the acuity of the presenting clinical syndrome, which may affect the degree of platelet inhibition required or achieved, influences the response to different antiplatelet agents. Methods and Results-A prospective, multicenter, double-blind, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
0
16
1
Order By: Relevance
“…15, 16 The TARGET trial, which also involved patients with unstable angina or non-ST-elevation MI, demonstrated that abciximab was superior to tirofiban in lowering the rates of MI at 30 days and 6 months; however, the 6-month mortality rates were identical for the abciximab and tirofiban groups. 17 In a more recent study of ST-segment elevation ACS, a double-bolus intravenous regimen of tirofiban did not demonstrate significant angiographic or clinical outcomes in patients undergoing PCI. 18 The 30-day ventricular function and cardiac events following primary PCI are determined by a number of factors, such as the size of the infarct, the status of coronary reperfusion, the use of medications, and presence of serum inflammatory factors such as interleukin-10.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…15, 16 The TARGET trial, which also involved patients with unstable angina or non-ST-elevation MI, demonstrated that abciximab was superior to tirofiban in lowering the rates of MI at 30 days and 6 months; however, the 6-month mortality rates were identical for the abciximab and tirofiban groups. 17 In a more recent study of ST-segment elevation ACS, a double-bolus intravenous regimen of tirofiban did not demonstrate significant angiographic or clinical outcomes in patients undergoing PCI. 18 The 30-day ventricular function and cardiac events following primary PCI are determined by a number of factors, such as the size of the infarct, the status of coronary reperfusion, the use of medications, and presence of serum inflammatory factors such as interleukin-10.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies of tirofiban have focused mostly on non-ST elevation ACS and their results have sometimes been inconsistent. 7,[15][16][17] The RESTORE investigators have shown in a large group of patients with unstable angina or acute MI that tirofiban reduced major cardiovascular events within 2 days following primary or nonprimary PCI; however, tirofiban did not improve the clinical outcomes or reduce coronary restenosis between day 2 and 6 months following the PCI. 15, 16 The TARGET trial, which also involved patients with unstable angina or non-ST-elevation MI, demonstrated that abciximab was superior to tirofiban in lowering the rates of MI at 30 days and 6 months; however, the 6-month mortality rates were identical for the abciximab and tirofiban groups.…”
Section: Discussionmentioning
confidence: 99%
“…73 Whether small-molecule GPIIb/IIIa inhibitors such as tirofiban and eptibatide, which lack these nonplatelet effects, are equally as effective in suppressing myonecrosis has never been appropriately tested in a large-scale, comparative, randomized trial, although abciximab was shown to be more effective than low-dose tirofiban in preventing peri-PCI myonecrosis in patients with ACS in the TARGET trial. 74 More recently, it has been recognized that the clinical benefits of GPIIb/IIIa inhibitors are offset by their propensity to increase bleeding and thrombocytopenia, complications strongly associated with subsequent mortality. 75 The direct thrombin inhibitor bivalirudin has demonstrated noninferior suppression of ischemic complications compared with administration of heparin plus GPIIb/IIIa inhibitors with significant reductions in bleeding in patients with ACS, 76 resulting in reduced all-cause and cardiac mortality in patients with ST-segment elevation-MI undergoing primary PCI.…”
Section: Pharmacology To Reduce Periprocedural MImentioning
confidence: 99%
“…7,15,16) Recently, the PRISM-PLUS clinical trial 17) reported that the addition of tirofiban to heparin reduced the thrombus burden of the culprit lesion and improved distal perfusion in patients with unstable angina or non-Q-wave myocardial infarction. However, our present study demonstrated that compared with primary stenting alone, a combination therapy of early administration of tirofiban and primary stenting for treatment of ST-se AMI did not provide additional benefits for normal coronary blood flow in the IRA, in reducing major cardiac events 7,15,16,19,20) The short-term clinical outcomes of primary PCI have been improved by adjunctive pharmacologic therapy with abciximab. 7,15,16) However, if complete reperfusion of the IRA is considered a successful therapeutic end point, the results were not different between balloon angioplasty alone and balloon angioplasty plus abciximab in the RAPPORT Trial 7) or between stenting alone and stenting plus abciximab in the CADILLAC Trial.…”
Section: Discussionmentioning
confidence: 66%